Building rating system: an instrument for building accessibility measurement for better indoor navigation by blind people. Issue 3 (16th September 2019) - Jeamwatthanachai, Watthanasak; Wald, Mike; Wills, Gary
Abstract : Purpose: The purpose of this paper is to create a building rating system (BRS) with its bottom-up design model that can be carried out manually and in the future automatically. Design/methodology/approach: The BRS is built on the basis of the structure of spatial representation framework for indoor navigation by people with visual impairment, which was validated with visually impaired people, and incorporated with building design standards and regulations from around the world. The BRS was afterwards validated by three groups of five experts in the related fields such as research and development, accessibility, and building and interior designs. Finally, the user evaluation was carried out by three focus groups of three experts in risk assessment to verify the usability of the system. Findings: This paper provides the design and methodology of the BRS used for classifying the accessibility in buildings into four levels of classification for people with visual impairment navigating around the buildings. This system is evaluated with system usability scales (SUS), which is found to be in a "Good" level on average (72.2 SUS scores). Research limitations/implications: Success criteria used in the space classification are mainly created for people with visual impairment at this stage; other disabilities requirements must be taken into account for the next stage of the development. Practical implications: The system can be carried out in the future automatically in the form of standalone software or plugins that can be integrated in buildings and interior design software to seek recommendations toward a creation of inclusive built environment. Originality/value: This paper presents a design architecture of BRS with its details, description and success criteria used in the space classification.